2018
DOI: 10.1002/tox.22578
|View full text |Cite
|
Sign up to set email alerts
|

2.45 GHz microwave radiation induced oxidative and nitrosative stress mediated testicular apoptosis: Involvement of a p53 dependent bax‐caspase‐3 mediated pathway

Abstract: Deleterious effects of MW radiation on the male reproduction are well studied. Previous reports although suggest that 2.45 GHz MW irradiation induced oxidative and nitrosative stress adversely affects the male reproductive function but the detailed molecular mechanism occurring behind it has yet to be elucidated. The aim of present study was to investigate the underlying detailed pathway of the testicular apoptosis induced by free radical load and redox imbalance due to 2.45 GHz MW radiation exposure and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 61 publications
1
16
0
1
Order By: Relevance
“…The above results suggested that under this condition, 220 MHz pulsed modulated RF could induce apoptosis in testis germ cells. Shahin’s report [30] also showed that 2.45 GHz RF (0.248 W/m 2 , 2 h/day for 15 days, 30 days and 60 days) induced testicular apoptosis with an increase of cleaved caspase 3 and BAX, as well as a decrease of BCL2 in a duration dependent manner. Testicular apoptosis may impede germ cell production and result in a reduction of sperm quality.…”
Section: Discussionmentioning
confidence: 97%
“…The above results suggested that under this condition, 220 MHz pulsed modulated RF could induce apoptosis in testis germ cells. Shahin’s report [30] also showed that 2.45 GHz RF (0.248 W/m 2 , 2 h/day for 15 days, 30 days and 60 days) induced testicular apoptosis with an increase of cleaved caspase 3 and BAX, as well as a decrease of BCL2 in a duration dependent manner. Testicular apoptosis may impede germ cell production and result in a reduction of sperm quality.…”
Section: Discussionmentioning
confidence: 97%
“…Oxidative and nitrosative stresses are known to be associated with deleterious effects on male reproduction, as they disrupt the integrity of sperm DNA and diminish the fertilizing potential of the reproductive cells due to collateral damage inflicted upon proteins and lipids in the sperm plasma membrane [22]. Excess free radical load due to increased reactive oxygen species and nitric oxide generation may cause severe testicular oxidative damage by causing peroxidation of lipids and formation of carbonyls [23].…”
Section: Discussionmentioning
confidence: 99%
“…Another animal study after the exposure to 2.45 GHz showed an alteration in testicular histoarchitecture, decreased seminiferous tubule diameter, sperm count, sperm viability, and serum testosterone level, along with increased total ROS, NO, MDA levels. The expression of p53, Bax, active-caspase-3 in testes was also upregulated, while the expression of Bcl-xL, Bcl-2, procaspase-3, and PARP-1 was reported to be downregulated [ 151 ].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Moreover, increased MDA level was noted due to an imbalance of charge in unsaturated fatty acids, which also triggers free radical production [ 154 ]. Exposure to microwave radiation causes apoptosis via the p53-dependent Bax-caspase-3-mediated pathway [ 151 ]. An increase in ROS and generation of NO starts producing free radicals, which can cause severe testicular oxidative damage in the form of lipid peroxidation and the formation of carbonyls [ 155 ].…”
Section: Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation